Application Segmentation , Targeting and Positioning in the UMKM Marketing Strategy in Indonesia - Galih Fahmi Fadhillah; Hoirul Anam; Mashudi . (JOURNAL OF SHARIA ECONOMICS, 2023)
The increasing number of Micro, Small and Medium Enterprises (UMKM) in Indonesia has prompted attention to effective marketing strategies to help UMKM achieve success in the increasingly fierce business competition. Segmentation, targeting and positioning (STP) are important concepts in a marketing strategy that can help UMKM identify and reach target markets more effectively. This study aims to analyze the application of STP in the marketing strategy of UMKM in Indonesia. The research method used is descriptive analysis by collecting data through literature studies and interviews with MSME owners and experienced marketing practitioners. The results of the study show that through segmentation, UMKM can provide products or services that are more relevant and better meet the needs of the target market. Targeting helps UMKM to optimize the use of their resources by focusing on segments that have the potential to generate higher sales and profits. Then positioning helps UMKM differentiate themselves and build a strong image, thus creating a competitive advantage in an increasingly fierce market competition. However, there are still several challenges faced by UMKM in implementing STP effectively, including limited resources, limited understanding of the concept, and the need to continuously monitor and adapt their marketing strategies according to market changes.